2015
DOI: 10.1093/cid/civ028
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Invasive Meningococcal Disease in Adults and Children in Canada Between 2002 and 2011: A Prospective Cohort Study

Abstract: Outcomes following IMD remain poor in this resource-rich setting in the 21st century. These data identify priorities for clinical management of adults and children with IMD, and provide prognostic information for affected patients and their families and cost-effectiveness analyses for meningococcal vaccine programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
2
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 25 publications
2
61
2
17
Order By: Relevance
“…The hospitalized patients are more likely to have their circulatory status monitored with early and aggressive management of shock. 2 Meningococcal septicaemia in children develops when the initial host response to infection becomes inappropriately amplified and dysregulated. After the initial presentation of fever and pharyngitis, the disease may progress to fulminant fatal disease with disseminated intravascular coagulation, hypotension, septic shock and ultimately organ failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hospitalized patients are more likely to have their circulatory status monitored with early and aggressive management of shock. 2 Meningococcal septicaemia in children develops when the initial host response to infection becomes inappropriately amplified and dysregulated. After the initial presentation of fever and pharyngitis, the disease may progress to fulminant fatal disease with disseminated intravascular coagulation, hypotension, septic shock and ultimately organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…11 Complications with hearing loss and seizures were also reported in children below five years of age. 2 The important risk factor in the disease development is the nasopharyngeal carriage. The human nasopharynx is the only known reservoir for Neisseria meningitidis and spread by droplets of respiratory or throat secretions from carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadarangani et al, studied the risk factors for death and complications, and found that age, shock, seizures, bruising, abnormal platelet count, symptoms onset within 24 hours of admission or admission to the intensive care unit were independently associated with death [38]. Similarly, we found that age, seizures/collapse/shock/ coma and abnormal platelet count were independently associated to death and heart failure was the main risk factor for death in all, non-vaccinated cases and septicaemia cases.…”
Section: Discussionmentioning
confidence: 99%
“…Уперше менінгококову інфекцію (МІ) описав Vieusseux у Швейцарії у 1805 р. Менінгокок (Neisseria meningitidis) уперше був ідентифікований у спинно-мозковій рідині хворого на менінгіт Weichselbaum у 1887 р. За даними ВООЗ, у 2000-ні роки МІ стала причиною 171 000 смертельних випадків у всьому світі [1]. Neisseria meningitidis викликає 500 000 ви-падків септицемії та менінгіту у світі щорічно.…”
Section: актуальність проблемиunclassified